Foreign Experience in Combating Corruption in the Economic Sphere - Antonova, O. M.; Tiazhyna, A. M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article analyzes the experience of foreign countries in preventing corruption in the economic sphere. It is proven that effective anti-corruption efforts are among the most pressing challenges of modern times. The study shows that corruption in different countries takes similar forms and affects the same areas regardless of whether it occurs in a developed or a developing country. The protection of national interests in combating corruption in the economic sphere is determined and ensured by the ability of state institutions to create mechanisms for the implementation and protection of the interests of the national economy. It is established that under current conditions there is a need to improve the methodology of indicator-based analysis of corruption as a factor influencing the provision of Ukraine’s economic security, the assessment of corruption risks, as well as the effectiveness of internal systems for its detection and prevention within public authorities and administration.